Filipino an essential grammar - Zamar, Sheila (Routledge, an imprint of Taylor & Francis Group, 2023)
"Filipino: An Essential Grammar is a comprehensive and practical reference guide introducing the key grammatical forms and structures in Filipino language. This book offers a detailed exploration of key phonological, morphological, and syntactic features of Filipino that are essential to achieving high levels of proficiency in the language. Across fourteen chapters are concise explanations of important grammatical categories and linguistic features relevant in the description of Philippine languages, complemented by examples relevant for everyday conversations and easy-to-understand rules for navigating Filipino grammar. Taking into consideration the most salient grammatical aspects that need to be presented by teachers and mastered by learners of Filipino, this is the ideal reference grammar for researchers, teachers and learners of Filipino language. This book is designed for both independent and class-based study by learners of Filipino at all levels"--Provided by publisher.